Understanding How Microorganisms Respond to Acid pH Is Central to Their Control and Successful Exploitation - Lund, Peter A.; De Biase, Daniela; Liran, Oded; Scheler, Ott; Mira, Nuno Pereira; Cetecioglu, Zeynep; Fernández, Estefanía Noriega; Bover-Cid, Sara; Hall, Rebecca; Sauer, Michael; O’Byrne, Conor (Frontiers in Microbiology, 2020)
Microbes from the three domains of life, bacteria, archaea and eukarya, share the need to sense and respond to changes in the external and internal concentrations of protons. When the proton concentration is high, acidic conditions prevail and cells must respond appropriately to ensure that macromolecules and metabolic processes are sufficiently protected to sustain life. While we have learned much in recent decades about the mechanisms that microbes use to cope with acid, including the unique challenges presented by organic acids, there is still much to be gained from developing a deeper understanding of the effects and responses to acid in microbes. In this perspective article, we survey the key molecular mechanisms known to be important for microbial survival during acid stress. We discuss the research approaches that have been taken to investigate the problem and highlight promising new avenues. We discuss the influence of acid on pathogens during the course of infections and highlight the potential of using organic acids in treatments for some types of infection. We explore the influence of acid stress on photosynthetic microbes, and on biotechnological and industrial processes, including those needed to produce organic acids. We highlight the importance of understanding acid stress in controlling spoilage and pathogenic microbes in the food chain. Finally, we invite colleagues with an interest in microbial responses to low pH to participate in the EU-funded COST Action project called EuroMicropH and contribute to a comprehensive database of literature on this topic that we are making publicly available.